2009
DOI: 10.1016/j.vaccine.2009.01.083
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-galactosylceramide is an effective mucosal adjuvant for repeated intranasal or oral delivery of HIV peptide antigens

Abstract: Mucosal delivery of vaccines against sexually transmitted pathogens is important to elicit strong immune responses at biologically relevant sites. However, inclusion of appropriate adjuvants is essential to overcome the inherent mucosal tolerance. We present evidence in support of the effectiveness of co-administering alpha-Galactosylceramide (α-GalCer) as an adjuvant with a CTL-inducing HIV envelope peptide, via either oral or intranasal route, to prime antigen-specific immune responses in multiple systemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 22 publications
(35 reference statements)
4
72
0
Order By: Relevance
“…The possibility that dietary lipids might contribute to iNKT cell activation is an exciting one. Supporting a possible role for oral lipid antigens, two studies have used orally-administered α-galactosylceramide as a vaccine adjuvant, and both studies reported a measureable result with oral administration (35,36). Studies of lipid antigens from commensal bacteria also support a role for lipids antigens in the digestive system (29,30,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that dietary lipids might contribute to iNKT cell activation is an exciting one. Supporting a possible role for oral lipid antigens, two studies have used orally-administered α-galactosylceramide as a vaccine adjuvant, and both studies reported a measureable result with oral administration (35,36). Studies of lipid antigens from commensal bacteria also support a role for lipids antigens in the digestive system (29,30,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were first anesthetized by i.p. injection of ketamine and xylazine hydrochloride and then administered 100 μg of each peptide with 2 μg of αGalCer intranasally as described previously (32,33). The animals were maintained with their heads in anteflexion until they regained consciousness.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of iNKT cells with a-Galcer was shown to interfere with the induction of oral tolerance [32]. This sparked interest in the application of a-Galcer as a mucosal adjuvant [33,34]. Oral administration of a-Galcer increases migration of lamina propriadendritic cells (LP-DCs) to mesenteric lymph nodes, which is suggestive of increased CCR7 expression by LP-DCs [35].…”
Section: Inkt Cellsmentioning
confidence: 99%
“…The unique modulatory properties of these cells has driven increasing interest in the therapeutic potential of a-Galcer and other novel iNKT cell activators [16,38]. The immunogenicity of an oral human immunodeficiency virus (HIV) vaccine was strongly enhanced by the inclusion of a-Galcer in the formulation [33].…”
Section: Inkt Cellsmentioning
confidence: 99%
See 1 more Smart Citation